2017
DOI: 10.7860/jcdr/2017/29575.10396
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 2% Nasal Mupirocin Ointment on Decreasing Complications of Nasotracheal Intubation: A Randomized Controlled Trial

Abstract: Introduction: In oral and maxillofacial surgeries, nasotracheal intubation is carried out to increase the surgeon's access to the oral cavity. During nasotracheal intubation the risk of trauma is higher than that in orotracheal intubation as there is passage of the tube through the mucosa of the nasal tract due to which bacteria might get transported into the trachea. Aim:To evaluate the effect of 2% nasal mupirocin ointment before and after nasotracheal intubation on decreasing the complications of intubation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The pooled results from 20 studies [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] accounting of 10,526 patients showed that nasal decolonization may be associated with a significantly decreased risk of overall SSI in patients after surgery (RR = 0.59, 95% CI 0.38-0.90; Fig. 3).…”
Section: Nasal Decolonization and The Risk Of Overall Ssis After Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…The pooled results from 20 studies [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] accounting of 10,526 patients showed that nasal decolonization may be associated with a significantly decreased risk of overall SSI in patients after surgery (RR = 0.59, 95% CI 0.38-0.90; Fig. 3).…”
Section: Nasal Decolonization and The Risk Of Overall Ssis After Surgerymentioning
confidence: 99%
“…The remaining 30 studies were subjected to full-text review to exclude those with irrelevant subjects or those that did not fully meet the inclusion criteria. Ultimately, 20 studies were included in the meta-analyses [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Study Selectionmentioning
confidence: 99%
“…The pooled results from 20 studies [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] accounting of 10,526 patients showed that nasal decolonization may be associated with a significantly decreased risk of overall SSI in patients after surgery (RR = 0.59, 95% CI Tang et al Ann Clin Microbiol Antimicrob (2020) 19:33 Fig. 3).…”
Section: Nasal Decolonization and The Risk Of Overall Ssis After Surgerymentioning
confidence: 99%
“…The pooled results from 20 studies [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] accounting of 10526 patients showed that nasal decolonization may be associated with a signi cantly decreased risk of overall SSI in patients after surgery (RR=0.59, 95% CI: 0.38−0.90; Figure 3). Random effects model was chosen to balance the statistical heterogeneity (p for Cochrane's Q test=0.000, I 2 =75.8%).…”
Section: Nasal Decolonization and The Risk Of Overall Ssis After Surgerymentioning
confidence: 99%